(untitled) (Journal of the College of Basic Education, 2022)
Using chemical path technique, thin films of CdS have been prepared with two different thicknesses on a glass substrate. An attempt to relating structure properties of cadmium sulphide (CdS ) thin film with variation of thickness was reported. X-ray diffraction (XRD) was used to characterize the samples. One peak of (111) orientation is appeared in X-ray chart indicating the cubic phase of the films